Chinese lending specifics and projects in the Caucasus region: A look into project-level data - Katja Kalkschmied (OrdnungsPolitisches Portal (OPO), 2022)
The Caucasus region has experienced an increasing inflow of Chinese official development finance in the last twenty years. The inflow accelerated after the countries of the Caucasus region became participants in the Belt and Road Initiative. Chinese finance into Eurasia aims to build energy and economic corridors linking the European and Asian continents. Natural resource endowments and the geographic location between the two continents are favorable for these ambitions, and so are recent geopolitical developments. The war between Russia and Ukraine revokes new interest in the Middle Corridor energy and goods transportation routes running via the Caspian Sea and the Southern Caucasus. Much is to win from the TransCaucasus corridors for China, the European Union, and the Southern Caucasus countries but also for Kazakhstan and Turkey. Much is to lose also. This article infers on Chinese endeavors and lending specifics in the Caucasus region by looking at project-level data from the years 2000-20017. It concludes that the Southern Caucasus countries need to strategically manage the development cooperation offers from China and other powers to make the new interest in the region beneficial for them. This requires taking measures to ensure that foreign-financed projects meet domestic needs and interests and become effective for domestic development.
Keywords: 330; Development finance; Caucasus; China; BRI